Strength Improvement of Soft Ariake Creek Clay Through Solidification by PFBC Coal Ash-based Geopolymer - Legrans, Roski R. I. (TEKNO, 2015)
This research has used the Pressurized Fluidized Bed Combustor (PFBC) coal ash as the prime material of geopolymer to solidify the soft Ariake creek clay. The objective of the research is to study the effect PFBC coal ash-based geopolymer for strength improvement of soft Ariake creek clay through the relationship between the unconfined compressive strength (qu) and both the curing period (t) and the mixture ratio (d). The results of the research give conclusions that mixture ratio provides a significant effect to the strength improvement of treated soil (p<0.01) compared to curing period (p>0.05), where the highest strength is achieved at ratio of 40 % among designated mixture ratio as the typical strength of very stiff soil (200-400 kPa). Keywords : PFBC, geopolymer, Ariake creek clay